Development of Herbal Toothpaste Formulation with Combination of Binahong and Stevia (Stevia Rebaudina) Leaves Extract and Lemon Juice - Hidayaturrahman Rahman (Universitas Muhammadiyah Surakarta, 2020)
Toothpaste is the most important thing for oral health. A common problem that is susceptible to society is dental caries caused by Streptococcus mutants. Stevia leaves are widely used as a natural sweetener for food and beverage products that have low calories and are beneficial for health. Binahong leaves have traditional medicinal properties such as antibacterial. The content of vitamin C on the skin of a lemon has the potential to whiten teeth and prevent thrush. These three natural ingredients are used to make toothpaste. This research aims to make an effective and safe herbal toothpaste using a combination of stevia leaf extract, binahong leaf, and lemon peel flavoring. Binahong leaf extract is taken by a maceration method with a storage period of 7 days, stevia leaf 5 days, and lemon peel 3 days. The volumes of stevia leaf extract, binahong leaf and lemon peel used for each formulation were 0 ml, 0.5 ml, 1 ml, and 1.25 ml. To obtain toothpaste that has efficacy and safety, a series of tests are carried out starting from the organoleptic test, homogeneity test, spreadability test, and pH test. The pH of the toothpaste produced during the three weeks of testing fulfilled the SNI standard (12-3524-1995), which was 8.08-8.69 while the spread of toothpaste was quite good when applied to a toothbrush.